2011
DOI: 10.1016/j.pain.2011.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Differential processing of laser stimuli by Aδ and C fibres in major depression

Abstract: Clinical studies have revealed that up to 92% of major depressed patients report pain complaints such as back or abdominal pain. Furthermore, patients suffering from depression exhibit increased superficial pain thresholds and decreased ischemic (deep) pain thresholds during experimental pain testing in comparison to healthy controls. Here, we aimed to investigate a putative role of Aδ- and C-fibre activation in altered pain perception in the disease. Laser-evoked potentials (LEPs) of 27 unmedicated depressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 56 publications
0
10
0
1
Order By: Relevance
“…Single subject averages were computed for each participant using a baseline from −100 to 0 ms. To quantify the quality of AEPs, signal-to-noise ratios (SNRs) were calculated for the stimulus NA in both groups (n = 30) based on a single subject level at electrode Fz. SNRs were obtained by dividing the absolute of the N1 peak amplitude by the root mean square of the baseline (−100 to 0 ms) in a time window of 100 −180 ms. AEPs were further analyzed only for those participants who had SNRs above 10 dB (N = 12), as well as peak morphologies discernible as N1 [43]. All statistical analyses were carried out on a fronto-central electrode (Fz), which is known to show strong N1 and MMN responses [27].…”
Section: Methodsmentioning
confidence: 99%
“…Single subject averages were computed for each participant using a baseline from −100 to 0 ms. To quantify the quality of AEPs, signal-to-noise ratios (SNRs) were calculated for the stimulus NA in both groups (n = 30) based on a single subject level at electrode Fz. SNRs were obtained by dividing the absolute of the N1 peak amplitude by the root mean square of the baseline (−100 to 0 ms) in a time window of 100 −180 ms. AEPs were further analyzed only for those participants who had SNRs above 10 dB (N = 12), as well as peak morphologies discernible as N1 [43]. All statistical analyses were carried out on a fronto-central electrode (Fz), which is known to show strong N1 and MMN responses [27].…”
Section: Methodsmentioning
confidence: 99%
“…It is known that chronic pain and major depression are correlated since depression is a common comorbidity of chronic pain and often chronic pain is an additional symptom of depressed patients [42, 43]. It has been confirmed by some studies that thresholds for acute painful stimulation are lower in depressed patients than in healthy controls [44, 45], whereas other studies found the opposite, namely, increased thresholds in depressed patients [42, 4649]. The physiological basis for pain perception, pain processing, and the sensitivity to painful stimuli of depressed patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Another somewhat surprising finding is that there are slightly more motifs in the post-stimulus period found in MD patients. It was previously found that MD patients compared to HC exhibit higher pain thresholds to external stimulation including electrical stimulation [48], [58], lower sensitivity to C-fiber activation [59], and/or lower sensitivity to experimental nociceptive stimulation [58], [60]. However, it should be mentioned that the stimulation was performed with stimuli that were adjusted for subjective pain ratings (i.e., moderately painful in both groups).…”
Section: Resultsmentioning
confidence: 99%